KALIMAT TIDAK BERKLAUSA DALAM BAHASA INDONESIA - I. Praptomo Baryadi (Widyaparwa, 2019)
This article discusses sentences without clauses in Indonesian. The discussion includes the type of intent, the type of speech act, level of politeness, and its function in verbal communication. The method used is the observation method for data collection, pragmatic identity methods for data analysis, and formal and informal methods for presenting the results of data analysis.The findings of this study are as follows. First, there are at least fifteen purposes contained in sentences without clauses, namely ‘praising’, ‘congratulating’or‘compassing’, ‘thanking’, ‘apologizing’, ‘forgiving’, ‘delivering greetings’, ‘greeting’ or’calling’, ‘approving’, ‘squealing’, ‘conveying information’, ‘giving confirmation’, ‘refusing’, ‘commanding’, ‘cursing’, and ‘threatening’.. Second, sentences without clauses in Indonesian can be grouped into four types of speech acts, namely (i) convivial speech acts consisting of ‘praising’,’congratulating’ or ‘compassing’, ‘thanking’, ‘apologizing’, ‘forgiving’; (ii) collaborative speech acts include sentences that intend to ‘delivering greetings’, ‘greeting’ or ‘calling’, ‘approving’, ‘squealing’ ; (iii) competitive speech acts covers sentences that intend to ‘conveying information’ and ‘giving confirmation’; (iv) conflictive speech acts including sentences that mean ‘refusing’, ‘commanding’ , ‘cursing’, and ‘threatening’. Third, the level of politeness of sentences without clauses in the Indonesian,  from the highest to the lowest is from sentences that include convivial speech acts, collaborative speech acts, competitive speech acts, and conflictive speech acts. Fourth, in verbal communication, the function of sentences without clauses in Indonesian is ideational, interpersonal, textual.Artikel ini membahas kalimat tidak berklausa dalam bahasa Indonesia. Pembahasannya mencakup jenis maksud, jenis tindak tutur, tingkat kesopanan, dan fungsinya dalam komunikasi verbal. Metode yang digunakan adalah metode simak dalam pengumpulan data, metode padan pragmatis dalam analisis data, dan metode formal serta informal dalam penyajian hasil analisis data. Temuan penelitian ini adalah sebagai berikut. Pertama, ada sekurang-kurangnya lima belas jenis maksud yang dikandung dalam kalimat tidak berklausa dalam bahasa Indonesia, yaitu ‘memuji’, ‘mengucapkan selamat’ atau ‘bela rasa’, ‘berterima kasih’, ‘meminta maaf’, ‘memaafkan’, ‘menyampaikan salam’, ‘menyapa’ atau ‘memanggil’,  ‘menyetuju’, ‘memekikkan’, ‘menyampaikan informasi’, ‘menyampaikan konfirmasi’,  ‘menolak’, ‘memerintah’, ‘memaki’, dan ‘mengancam’.  Kedua, kalimat tanpa klausa dalam bahasa Indonesia dapat dikelompokkan ke dalam empat jenis tindak tutur, yaitu (i) tindak tutur konvivial meliputi kalimat yang bermaksud 'memuji', 'mengucapkan selamat' atau ‘bela rasa’, 'berterima kasih', 'meminta maaf', dan 'memaafkan'; (ii) tindak tutur kolaboratif mencakup kalimat yang bermaksud 'menyampaikan salam', 'menyapa' atau 'memanggil', 'menyetujui’, dan ‘memekikkan'; (iii) tindak tutur kompetitif terdiri atas kalimat yang bermaksud 'menyampaikan informasi' dan 'menyampaikan konfirmasi'; (iv) tindak tutur konfliktif meliputi kalimat yang bermaksud 'menolak', 'menyuruh', 'memaki', dan 'mengancam'. Ketiga, tingkat kesopanan kalimat tidak berklausa dalam bahasa Indonesia,  dari yang paling tinggi sampai yang paling rendah adalah dari kalimat yang termasuk tindak tutur konvivial, tindak tutur kolaboratif, tindak tutur kompetitif, sampai tindak tutur konfliktif. Keempat, dalam komunikasi verbal kalimat tidak berklausa dalam bahasa Indonesia memiliki fungsi ideasional, interpersonal, dan tekstual.